CHILDREN UNDER ISLAMIC LAW - Mohd Al-Adib Samuri, (2025)
Children under Islamic Law examines many aspects of children’s lives and rights within the framework of Islamic Law in a comprehensive and insightful way. The book explores various facets of children’s experiences, such as their identity, education, welfare and protection, as viewed through the lens of classical Muslim jurists and contemporary scholars. In this essential resource, the contributing authors examine diverse topics such as the definition of children in Islamic jurisprudence, their participation in religious activities, the role of Takaful (Islamic insurance) in safeguarding their future, and the significance of Hibah (gift) in supporting their well-being. Furthermore, the book provides an in-depth analysis of the Zakat (almsgiving) system and its impact on homeless children, the Islamic perspective on wet nursing, and the importance of vaccination in safeguarding their health. The book delves into the complex arena of children’s rights when they are in conflict with Islamic criminal law, offering an insightful examination of the pre-trial procedures designed to protect and support children. This book is an indispensable resource for scholars, students and practitioners in the fields of Islamic studies, law, sociology and child welfare. Providing a holistic understanding of the rights and responsibilities of children within the Islamic legal system contributes to the ongoing conversation on the best interest of the child and helps bridge the gap between traditional Islamic values and contemporary needs.